Reconfiguration of DNA methylation in aging - Zampieri, Michele; Ciccarone, Fabio; Calabrese, Roberta; Franceschi, Claudio; Bürkle, Alexander; Caiafa, Paola (Mechanisms of ageing and development, 2015)
•Methylated cytosines have a non-random distribution throughout the genome.•DNA methylation patterns are dynamic states balanced by methylation and demethylation.•Environmental exposure and lifestyle impact the genomic methylation patterns.•Dynamic reprogramming of DNA methylation patterns in aging A complex interplay between multiple biological effects shapes the aging process. The advent of genome-wide quantitative approaches in the epigenetic field has highlighted the effective impact of epigenetic deregulation, particularly of DNA methylation, on aging. Age-associated alterations in DNA methylation are commonly grouped in the phenomenon known as “epigenetic drift” which is characterized by gradual extensive demethylation of genome and hypermethylation of a number of promoter-associated CpG islands. Surprisingly, specific DNA regions show directional epigenetic changes in aged individuals suggesting the importance of these events for the aging process. However, the epigenetic information obtained until now in aging needs a re-consideration due to the recent discovery of 5-hydroxymethylcytosine, a new DNA epigenetic mark present on genome. A recapitulation of the factors involved in the regulation of DNA methylation and the changes occurring in aging will be described in this review also considering the data available on 5hmC.